2021
DOI: 10.33808/clinexphealthsci.852450
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of the Abrasiveness for Resin Composite Finishing & Polishing Systems

Abstract: Objective: This study was aimed to assess the abrasiveness of 4 composite finishing and polishing systems, on 2 nano-hybrid composite materials.Methods: Fourty samples were prepared using Tetric EvoCeram BulkFill and IPS Empress Direct composites (Ivoclar Vivadent, Schaan, Lichtenstein). Each group was divided into 4 subgroups (Sof-Lex Disc, 3M, MN,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…In the present study, the majority of cases in group A (celluloid matrix) reported a score of (3) at all intervals, denoting that form deviates from normal but is aesthetically accepted, while most of the cases in group B (bioclear matrix) had a score of (2), denoting form only slightly deviates from the normal. According to Bansal et al, (2019) [ 28 ] and Korkut and Unal, (2021) [ 29 ], proper finishing, polishing, and proper selection of resin composite type in the form of nanohybrid resin composite were associated with successful restorative management. This justifies the success of all cases in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the majority of cases in group A (celluloid matrix) reported a score of (3) at all intervals, denoting that form deviates from normal but is aesthetically accepted, while most of the cases in group B (bioclear matrix) had a score of (2), denoting form only slightly deviates from the normal. According to Bansal et al, (2019) [ 28 ] and Korkut and Unal, (2021) [ 29 ], proper finishing, polishing, and proper selection of resin composite type in the form of nanohybrid resin composite were associated with successful restorative management. This justifies the success of all cases in both groups.…”
Section: Discussionmentioning
confidence: 99%